Exploring Contextual Teaching Effects on Student Motivation in Elementary Language Learning - Alma Safira; Yusdin B M Gagaramusu; Khairunnisa Khairunnisa; Muhammad Fasli; Nurul Fitria Fitria Aras; Surahman Wilade (Journal of Innovation and Research in Primary Education, 2026)
Low student motivation in Indonesian language learning at the elementary level remains a persistent pedagogical challenge, often stemming from conventional teaching approaches that fail to connect academic content with students' lived experiences. This study examined the effect of Contextual Teaching and Learning (CTL) on fourth-grade students' learning motivation in Indonesian language instruction. A quasi-experimental one-group pretest-posttest design was employed with 28 fourth-grade students at Al-Khairaat Tondo Elementary School, Palu City, Indonesia. Data were collected through learning motivation questionnaires, classroom observations, semi-structured interviews, and documentation. Analysis included descriptive statistics, Shapiro-Wilk normality test, and paired-samples t-test. Observational data revealed high student engagement (80-100% participation), with most students categorized as having Good (n=13) or Very Good (n=6) motivation levels post-intervention. Descriptive statistics showed an increase in mean scores from 64.27 (pretest) to 69.12 (posttest). However, inferential analysis indicated this difference was not statistically significant, t(24) = -0.716, p = 0.481. While CTL implementation was associated with enhanced classroom engagement and positive motivational responses, the intervention did not produce statistically significant changes in self-reported motivation. The findings suggest CTL holds pedagogical value for fostering participatory learning environments but requires extended duration and complementary autonomy-supporting strategies to generate measurable motivational shifts. Future research should employ control-group designs with longer intervention periods.